Petan Kebijakan Fiskal Dalam Mendukung Pembangunan - Lawodi, Elvina; Agustin, Mira; Totoro'o, Olivia (Fakultas Ekonomi Universitas KristenTentena, 2025)
This study aims to understand the extent to which fiscal policy can support sustainable economic development. I employed a literature review approach and analyzed secondary data related to fiscal policy, the state budget (APBN), and taxation instruments. The analysis indicates that well-targeted fiscal policies—through both government spending and tax revenues—can promote more equitable economic growth, reduce poverty, and support environmental sustainability. These findings suggest that policy reforms, such as enhancing budget efficiency and implementing a fairer taxation system, play a crucial role in achieving sustainable development goals.